2022
DOI: 10.1021/acs.chemmater.2c00851
|View full text |Cite
|
Sign up to set email alerts
|

Surface Acidity-Induced Inherently Selective Atomic Layer Deposition of Tantalum Oxide on Dielectrics

Abstract: Selective deposition shows a great perspective for the downscaling of nanoelectronics. In this work, inherently selective atomic layer deposition (ALD) of tantalum oxide was studied on a series of oxide substrates. The Ta2O5 films linearly grow on acidic oxides of MnO2, SiO2, and Ta2O5, while there are long nucleation delays on basic oxides such as Al2O3 and HfO2. The inherent selectivity is induced through acidity differences which influence the reaction path, and the H-transfer reaction is a key factor. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 71 publications
1
11
0
Order By: Relevance
“…5 and 6 ), indicating that smooth film was obtained. For the ABC-type ALD, it was found that the growth rate of Ta 2 O 5 on Al 2 O 3 and HfO 2 was lower than that on SiO 2 , which confirmed the occurrence of previously reported surface acidity-induced selective deposition 55 . A total of 10 s purge time was sufficient to remove excess precursors and by-products.…”
Section: Resultssupporting
confidence: 88%
“…5 and 6 ), indicating that smooth film was obtained. For the ABC-type ALD, it was found that the growth rate of Ta 2 O 5 on Al 2 O 3 and HfO 2 was lower than that on SiO 2 , which confirmed the occurrence of previously reported surface acidity-induced selective deposition 55 . A total of 10 s purge time was sufficient to remove excess precursors and by-products.…”
Section: Resultssupporting
confidence: 88%
“…Hacac exhibits primarily acidic characteristics and therefore preferentially bonds with more basic surfaces, such as Al 2 O 3 , ZrO 2 , and HfO 2 , rather than the acidic SiO 2 . According to the literature, 25,45,46 copper oxides have comparable or even lower surface acidity values than the above-mentioned metal oxides, and native oxide covered Cu is therefore expected to bond strongly with Hacac. The adsorbed molecules passivate the substrate surfaces and thereby prevent the ALD growth, which is proposed to be a mechanism for the current observation of selective growth of Ir on native SiO 2 over Cu.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…A similar approach can be taken in matching the SMI with a specific substrate, as was illustrated by Li et al in evaluating tantalum oxide deposition on acidic (MnO 2 , SiO 2 , Ta 2 O 5 ) and basic (Al 2 O 3 and HfO 2 ) oxide surfaces. 54 Nevertheless, for any series of chemically similar or homologously different substituents in SMIs, the role of steric effects clearly offers a great handle for using bulkier precursors to improve the selectivity, provided that changing the precursor does not affect all of the other constraints.…”
Section: Steric Hindrance Geometry Packing and Precursor Of Choicementioning
confidence: 99%
“…Thus, a different measure has to be involved to evaluate the role of electronic factors, as is summarized in the same Figure in panels B and D using the charge of surface hydrogen atom to be transferred to an amino group in the attachment reaction or a measure of surface acidity/basicity. A similar approach can be taken in matching the SMI with a specific substrate, as was illustrated by Li et al in evaluating tantalum oxide deposition on acidic (MnO 2 , SiO 2 , Ta 2 O 5 ) and basic (Al 2 O 3 and HfO 2 ) oxide surfaces …”
Section: Basic Requirements and Preliminary Criteria For Smi Propertiesmentioning
confidence: 99%